Enhancing Financial Transparency and Corporate Governance in Financial Reporting: An Impact Analysis of IFRS Adoption - Anggraeni, Rasmi Nur (Yayasan Sinergi Kawula Muda, 2023)
This study evaluates the impact of International Financial Reporting Standards (IFRS) adoption on financial reporting quality, focusing on transparency, earnings management, capital market access, and industry-specific effects. Using a systematic literature review across multiple jurisdictions, the findings indicate that IFRS generally enhances financial transparency and facilitates cross-border investment. However, its effectiveness depends heavily on strong regulatory enforcement and corporate governance. While several studies report reduced earnings management due to stricter standards, opportunistic practices may still persist, particularly in regions with weaker oversight. IFRS adoption also tends to improve access to capital markets, but challenges remain, including high implementation costs, regulatory inconsistencies, and limited resources, especially in developing economies. The study acknowledges limitations such as potential publication bias and varying regional contexts that may influence IFRS outcomes. To maximize the benefits of IFRS, the study recommends strengthening legal frameworks, investing in training for accounting professionals, and fostering collaboration between international standard setters and local regulators. These measures aim to enhance compliance, reduce complexity, and improve overall financial reporting quality globally.